Digital transformation and determinants of business growth in the IS/IT consulting sector - Ramos, B.; Ferreira, F.; Ferreira, N.; Ferreira, J.; Falcão, P. (Strategic Change, 2025)
In an era marked by profound societal transformations and disruptions, companies in the information systems and technologies (IS/IT) consultancy sector face increasing pressure to rethink their growth strategies and secure sustained competitive advantages. Digital transformation, as a key megatrend, plays a central role in reshaping this sector, reflecting the complexity of the current market and the disruptive influence of information and communication technologies (ICT) on both business and society. This study provides a novel contribution by integrating the extensive body of literature on digital transformation with strategic decision-making in the IS/IT consultancy sector, focusing specifically on the growth dynamics of Axians Portugal. Employing Interpretive Structural Modeling (ISM), a sophisticated methodology for structuring complex, multi-dimensional causal relationships, this research systematically analyzes key determinants of growth for the company. By adopting a collaborative and constructivist approach, the study engages the organization in a strategic reflection process, enabling a deeper understanding of the interdependencies that shape growth decisions. The practical impact is significant, as Axians Portugal validated the key results and actionable strategies for enhancing growth in the ICT consultancy landscape. Theoretical implications are discussed in terms of advancing the understanding of digital transformation within consultancy contexts, while the study's limitations are also acknowledged. This work contributes to both theory and practice by offering a framework for IS/IT consultancy firms to navigate the complexities of digital transformation and strategically position themselves for long-term success.